Pengaruh Industri Besar, Nilai Investasi Besar, PDRB Sektor Industri dan Perdagangan Terhadap Penerimaan Pajak Reklame di Kota Jambi Tahun 2011-2020 - Fathiyah Fathiyah; Ira Febrianti (Universitas Batanghari, 2021)
This research aims to find out how much influence Large Industry, Large Industrial Investment Value and PDRB Sector (Industry and Trade) on Billboard Tax Revenue in Jambi City 2011-2020 both partially and simultaneously. The statistical method used is a double linear regression analysis including Test F and Test t. Ols double linear regression research results show that partially Large Industries, Large Industrial Investment Values and Sector PDRB (Industry and Trade) have a significant effect on Billboard Tax Revenue in Jambi City. While simultaneously showing that the influence of Large Industries, Large Industrial Investment Value and PDRB Sector (Industry and Trade) affects the Receipt of Billboard Tax in Jambi City together. The Independent Variable coefficient of determination affects dependent variables by 97.94% while the remaining 2.06% is influenced by other factors not described in the study.